Patrick Faigenbaum. - Chevrier, Jean-François (Paris : Editions Hazan Paris, 2000)
The French language, like English, relates statuary to the stature of the model fixed by recording. Patrick Faigenbaum has never ceased working with the Family relation, at once simple and strange. For him as for Brassaï (the photographer of Picasso's sculptures, the portraitist obsessed by the plastic presence of bodies subject to gravity) recording is a petrifying fountain. Patrick Faigenbaum is a photographer of this plastic presence, revised by the snapping shutter. What Brassaï called the Living Thing is gripped by a process of mineralization, is fixed in the immutable form of a Dream of Stone (Baudelaire). Patrick Faigenbaum is a photographer of slowness : the slow movement of living matter animated by its impulsion toward statuary. And as always in his work, this tendency is a matter or play of relation.
biog., ind. tent., gr. tent., bibliog. p. 110-111
Engels
Frans
boek
Keywords: Faigenbaum, Patrick